Successful endodontic treatment on an upper lateral incisor with non-perforating inflammatory internal root resorption: case report (Research, Society and Development, 2020)
Internal tooth resorption is usually asymptomatic and is almost always diagnosed on routine radiographic examinations. The objective of this study is to present a clinical case report of a tooth affected by internal non-perforating inflammatory root resorption, in order to disseminate information that can be used to guide professionals in these cases, helping with therapeutic management. A 53-year-old female patient was referred to the specialization course at Faculdade CIODONTO after performing a routine periapical radiographic examination, which showed non-perforating internal resorption at the level of the radicular middle third of the tooth 12. Radiographically it was verified that the contour of the pulp boundaries undergoes a relatively symmetrical expansion with a ballooning aspect, with regular and rounded contours. After coronary opening, bleeding compatible with the vital pulp was observed, initially irrigating with lime water. Biomechanical preparation using the crown-apex technique without pressure was performed and Callen was selected as an intracanal medication for 30 days and L&C paste for 90 days. After this period, root canal filling was performed using the Tagger hybrid thermoplastic technique and calcium hydroxide-based endodontic cement. Proservation was performed after 1 year and the success of endodontic therapy was confirmed. Thus, according to the protocol indicated in the literature, effective clinical resolution of teeth affected by internal non-perforating resorption is allowed, proving to be an excellent alternative for conservative treatment.